A study of the mechanical structure of the direct roof during the whole process of non-pillar gob-side entry retaining by roof cutting. Issue 5 (September 2020) - Liu, Xiao; Hua, Xinzhu; Yang, Peng; Huang, Zhiguo
The non-pillar entry (roadway) retained by roof cutting serves the two adjacent working faces. As compared with the conventional mining roadways, the roadway retained by roof cutting has a longer life cycle and receives more complicated influence from mining. Determining the location where the roof deformation and maximum deformation occur can provide an important basis for roadway support. Here, the direct roof of the roadway is studied by assuming it as an elastic deformation body. The stress features of the direct roof of the gob-side entry retained by roof cutting are analyzed, and the roof deformation is divided into five stages. The stress superposition principle is employed, and the equivalent concentrated load within the roadway is introduced. The mechanical model of the direct roof is established for the whole process of gob-side entry retaining by roof cutting. Next, the calculation formula for the concentration of direct roof at different positions is obtained for the whole process of gob-side entry retaining by roof cutting. The application scope of the calculation formula and the determination method of the key parameters are analyzed. The relationship between direct roof deformation of the roadway and stiffness of the support system is studied. The results show that the direct roof deformation has a symmetrical distribution about the midline. The maximum roof deformation occurs in the middle of the roadway, and it gradually decreases as the coal seam stiffness increases. During the example calculation, the maximum roof deformation is 280 mm for the gob-side entry retaining under primary mining. The measured maximum roof deformation is 320 m, and the error rate is 12.5%. It is then verified that the uniform mechanical model proposed in this study applies to the calculation of direct roof deformation in the gob-side entry retained by roof cutting.